Angle Class I malocclusion with anterior negative overjet - Souza,Paulo Ávila de (2016)
ABSTRACT This clinical case report describes the orthodontic treatment of an 8-year and 9-month old female patient with Angle Class I malocclusion, anterior crossbite and canine Class III relationship. Orthodontic treatment was carried out in two stages. The first one was orthopedic, while the second one included the use of a fixed appliance and the need for space gain for reshaping of maxillary lateral incisors. The two-stage treatment combined with multidisciplinary Restorative Cosmetic Dentistry allowed excellent esthetic and functional outcomes to be achieved. This case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as a requirement for the title of certified by the BBO.